Dividend announcements and share price dynamics: new evidence from Saudi-listed companies using event study approach - Abaalkhail, Layla; McCluskey, Thomas; Power, David (Frontiers in Applied Mathematics and Statistics, 2025)
Although a considerable number of empirical studies have been conducted in developed markets to examine dividend signaling effects, very few comparable studies have been carried out in the Saudi market context. This study deeply investigates how the Saudi exchange market may have reacted to dividend news during an eight-year study period from a total sample of 280 dividend announcements made by 99 Saudi-listed companies. Results demonstrate that a company’s share price reacts to the announcement of a cash dividend during the event window. Besides, findings reveal a significant positive reaction in the share price at the time of the announcement of an increase in the dividend payment level. Furthermore, results demonstrate that the abnormal return is negative but not significantly different from zero at the time of the announcement of a decrease in the dividend payment level. Likewise, findings show that the shareholders earn just normal returns on the announcement day and that the abnormal return is not statistically different from zero for the dividend, not change group. The findings suggest potential information leakage before dividend announcements, raising concerns about insider trading. This highlights the need for stronger regulatory oversight and stricter disclosure enforcement. Companies should also use alternative communication channels to improve transparency and consider corporate social responsibility initiatives to signal their quality to investors.